Where do Babies Come From? - Marilyn Eshikena (Voices in Bioethics, 2014)
A relatively novel procedure has joined the frontiers in reproductive technology.  As the world watches and waits for its absolute success, it serves as a source of hope for a group of women without the vessel for child conception. This procedure is known as womb transplantation and was successfully carried it in nine women in Sweden, but it leads to important ethical dilemmas. The nine women, some born without uteri and others void of uteri as a result of hysterectomies, received donor wombs from close relatives. These transplanted wombs have been, at the moment, pronounced temporary. It is said that after two pregnancies, these uteri will be removed from the women, so that they can be weaned of anti-rejection medication. Before this technology, these women would have to opt for adoption or surrogacy. However, in certain European countries like Sweden, surrogacy is prohibited. Thus, these women are left with limited possibilities to mother children. However, with womb transplantation, they have been given an opportunity to, not only have wombs, but to have full term pregnancies and birth healthy children.